Notch Signaling Pathway and Human Placenta - Zhao, Wei-Xiu (Ivyspring International Publisher, 2012)
Notch signaling was evolutionarily conserved and critical for cell-fate determination, differentiation and many other biological processes. Growing evidences suggested that Notch signaling pathway played an important role in the mammalian placental development. All of the mammalian Notch family proteins had been identified in human placenta except Delta-like 3, which appeared to affect the axial skeletal system. However the molecular mechanisms that regulated the Notch signaling pathway remained largely unknown in human placenta. Therefore, additional research was needed to investigate expression pattern of Notch family members and the mechanisms for activation of Notch signaling pathway in human placenta, which might help elucidate the roles of Notch signaling pathway in human placentation. This review would focus on the roles of Notch receptors and ligands in the human placental trophoblasts function and placental angiogenesis. It might hopefully provide perspectives for future research about human placentation of pregnancy complicated by preeclampsia and other placenta associated diseases.